'The more South you go, the more frankly you can speak': Metronormativity, critical regionality and the LGBT movement in Salento, South-Eastern Italy. (January 2019) - Ammaturo, Francesca Romana
In recent times, the region of Salento in South-Eastern Italy has become one of the most popular gay-friendly tourist spots in the country and several LGBT organisations have operated in this territory over the last few years. This article seeks to map the creation, development and challenges of the LGBT movement in this Italian sub-region by looking at forms of negotiation between 'local' and 'queer' identities and beyond narratives of 'metronormativity' of LGBT identities and from the perspective of 'critical regionality' and 'meridian thought'. Through semi-structured interviews conducted with five local LGBT activists in 2016 and ethnographic observations carried out at Pride events in 2016 and 2017, the article looks at conflicting social processes whereby local activism is rooted in situated allegiances and interactions with the territory and its population, whilst being permeated by the globalising dynamics of LGBT identity politics.